The stratigraphic and structural setting of metamorphic continental units from Alpine Corsica: clues from the area between Asco and Golo valleys (Central Corsica, France). Issue 2 (9th December 2020) - Malasoma, A.; Morelli, G.; Di Rosa, M.; Marroni, M.; Pandeli, E.; Principi, G.; Pandolfi, L.
ABSTRACT: The area between the Asco and Golo valleys in Central Corsica, France (latitudes 42°47′95″N to 42°37′96″N, longitudes from 9°11′82″E to 9°20′72″E) is a key-sector to investigate the stratigraphic and tectonic setting of Alpine Corsica. This sector includes (from the structurally lowest to the highest) the Hercynian Corsica, that represents the European continental margin not deeply involved in the convergence processes, and a stack of oceanic and continental units belonging to the Alpine Corsica, i.e. the domain strongly affected by the Alpine deformation and metamorphism in the Late Cretaceous-Paleogene. The 1:15, 000 scale geological map illustrates the tectonic features of Alpine Corsica stack with a special focus to the Lower Units, the units derived from the European thinned continental margin involved in the Alpine convergence.